Prevalence of Hepatitis B in HIV infected persons: choice of antiretroviral therapy regimen and implications for screening - Reidy, Derval (Department of Public Health and Family Medicine, 2015)
Limited data and few studies have shown the prevalence of Hepatitis B in the HIV infected population in South Africa, whether these patients are on appropriate antiretroviral therapy and the effect of Hepatitis B on liver function in co-infected persons. The objectives of this study were to determine the prevalence of Hepatitis B surface antigemia (HBsAg) in healthy HIV positive persons screened for a vaccine trial and the proportion of those eligible for antiretroviral therapy that were receiving optimal antiviral treatment, namely tenofovir and/or lamivudine. The relationship between Hepatitis B carriage and liver function was also determined in co-infected persons as measured by liver function tests. A cross sectional study was conducted from 30th August 2011 to 24th April 2013 to determine the prevalence of HIV /HBV co-infection in persons attending a clinical trial site in an urban clinical trials unit of Cape Town. Participants self-presented to the clinic and once consented were enrolled into the study and provided blood for HIV confirmatory test, Hepatitis B sAg, CD4, VL, full blood count, liver function and renal function tests. 638 participants were enrolled into this cross sectional study. 24 (3.8%) were Hepatitis B sAg positive, which was lower than expected. Of the 24 HIV/HBV co-infected participants, 19 (79 .2%) were on antiretroviral therapy, 14 (73. 7%) of these were on a tenofovir/lamivudine regimen the remaining 5 (26.3%) were not on a tenofovir regimen. Five of the co-infected participants were not on ARVs because their CD4 count was above the recommended South African guidelines for treatment i.e. greater than 350 1 QA6/l. Male participants were three times more likely to be HBsAg positive. Elevated Alanine aminotransferase (ALT) and Aspartate Aminotransferase (AST) were associated with HBsAg seropositivity. This study showed a lower HIV /HBV co-infection prevalence rate than reported from other locations in South Africa suggesting geographical variability. Appropriate guidelines are required to ensure that co-infected patients are identified and treated with the most appropriate anti-retroviral regimens. Screening for HBV is also recommended in HIV infected cohorts.